Use of Cortisol and Adrenal Weight at Pediatric Postmortem. (4th May 2017) - Morrison, Rebecca; Khan, Jansher; Galloway, Peter; McNeilly, Jane; Ahmed, Syed Faisal; Penman, Dawn
ABSTRACT: We studied the relationship between adrenal weight and postmortem cortisol level in cases of infant death, and examined use of these measurements in adrenal insufficiency. We analyzed procurator-fiscal postmortem reports in the West of Scotland over a three year period. Combined adrenal weight was expressed as percentage of total body weight (%TBW). Of 106 cases, median (5 th, 95 th ) %TBW was 0.056 (0.025, 0.23) and median plasma cortisol was 8.4 ug/dl (1.0, 47.1). There was no correlation between %TBW and plasma cortisol ( r = 0.09, p = 0.4). The lowest and highest plasma cortisol quartile had medians of 1.9 ug/dl (1.0, 3.4) and 34.3 ug/dl (17.3, 71.5), respectively. Infection was present in 6 cases (23.1%) in the lowest quartile and in 16 cases (61.5%) in the highest quartile ( p = 0.01). Our results highlight the difficulty in interpretation of cortisol at postmortem and suggest that adrenal weight measurement alone may be insufficient for diagnosis of adrenal insufficiency.